Neuronal surface P antigen (NSPA) modulates postsynaptic NMDAR stability through ubiquitination of tyrosine phosphatase PTPMEG - Espinoza, Sofia; Arredondo, Sebastian B.; Barake, Francisca; Carvajal, Francisco; Guerrero, Fernanda G.; Segovia-Miranda, Fabian; Valenzuela, David M.; Wyneken, Ursula; Rojas-Fernandez, Alejandro; Cerpa, Waldo; Massardo, Loreto; Varela-Nallar, Lorena; et al. (My University, 2020)
BackgroundCognitive dysfunction (CD) is common among patients with the autoimmune disease systemic lupus erythematosus (SLE). Anti-ribosomal P autoantibodies associate with this dysfunction and have neuropathogenic effects that are mediated by cross-reacting with neuronal surface P antigen (NSPA) protein. Elucidating the function of NSPA can then reveal CD pathogenic mechanisms and treatment opportunities. In the brain, NSPA somehow contributes to glutamatergic NMDA receptor (NMDAR) activity in synaptic plasticity and memory. Here we analyze the consequences of NSPA absence in KO mice considering its structural features shared with E3 ubiquitin ligases and the crucial role of ubiquitination in synaptic plasticity.ResultsElectrophysiological studies revealed a decreased long-term potentiation in CA3-CA1 and medial perforant pathway-dentate gyrus (MPP-DG) hippocampal circuits, reflecting glutamatergic synaptic plasticity impairment in NSPA-KO mice. The hippocampal dentate gyrus of these mice showed a lower number of Arc-positive cells indicative of decreased synaptic activity and also showed proliferation defects of neural progenitors underlying less adult neurogenesis. All this translates into poor spatial and recognition memory when NSPA is absent. A cell-based assay demonstrated ubiquitination of NSPA as a property of RBR-type E3 ligases, while biochemical analysis of synaptic regions disclosed the tyrosine phosphatase PTPMEG as a potential substrate. Mice lacking NSPA have increased levels of PTPMEG due to its reduced ubiquitination and proteasomal degradation, which correlated with lower levels of GluN2A and GluN2B NMDAR subunits only at postsynaptic densities (PSDs), indicating selective trafficking of these proteins out of PSDs. As both GluN2A and GluN2B interact with PTPMEG, tyrosine (Tyr) dephosphorylation likely drives their endocytic removal from the PSD. Actually, immunoblot analysis showed reduced phosphorylation of the GluN2B endocytic signal Tyr1472 in NSPA-KO mice.ConclusionsNSPA contributes to hippocampal plasticity and memory processes ensuring appropriate levels of adult neurogenesis and PSD-located NMDAR. PTPMEG qualifies as NSPA ubiquitination substrate that regulates Tyr phosphorylation-dependent NMDAR stability at PSDs. The NSPA/PTPMEG pathway emerges as a new regulator of glutamatergic transmission and plasticity and may provide mechanistic clues and therapeutic opportunities for anti-P-mediated pathogenicity in SLE, a still unmet need.
Keywords: nmda receptor; glun2b tyr1472; tyrosine phosphatase ptpmeg; ptpn4; synaptic plasticity; memory; postsynaptic densities; ubiquitination; nspa; zzef1; npsle